Implementasi Program Mutaba’ah Yaumiyyah dalam Membentuk Religiositas Santri Kelas VIII PPTQ BMM Masfiah Rasyid Bogor - Paramansyah, Arman; Ernawati, Ernawati; Saidah, Chaira; Ramadini, Safira (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Pondok Pesantren is an Islamic educational institution that is very thick with religious values. The education system that lasts for 24 hours is a distinct characteristic of Islamic boarding schools. It is not surprising that the weight of learning and activities is much denser when compared to schools in general. The purpose of this study was to determine the implementation of the Mutaba'ah Yaumiyyah program (Journal of Daily Worship Evaluation) in shaping the religiosity of class VIII students at the Tahfidz Qur'an Islamic Boarding School (PPTQ) Community Development Independent (BMM) Masfiah Rasyid Bogor. The research method used is descriptive qualitative with a case study approach which produces data in the form of written descriptions of certain phenomena and behaviors according to facts or findings in the field. The results of this study can be concluded that: (1) The Yaumiyyah Mutaba'ah Program has been implemented quite well in terms of controlling, giving rewards and punishments, providing motivation, and filing Yaumiyyah Mutaba'ah forms. (2) There is an effectiveness value from the implementation of the Mutaba'ah Yaumiyyah program in shaping the religiosity of students, especially class VIII. This is evidenced by the increased awareness of students in worship and changes in morals for the better after the implementation of the Mutaba'ah Yaumiyyah program. (3) There are supporting and inhibiting factors in the process of implementing the Mutaba'ah Yaumiyyah program. Keywords: Implementation, Mutaba'ah Yaumiyyah, Religiosity